CDC27 Promotes Tumor Progression and Affects PD-L1 Expression in T-Cell Lymphoblastic Lymphoma - Song, Yue; Song, Wei; Li, Zhaoming; Song, Wenting; Wen, Yibo; Li, Jiwei; Xia, Qingxin; Zhang, Mingzhi (Frontiers in Oncology, 2020)
T-lymphoblastic lymphoma (T-LBL) is a rare hematological malignancy with highly aggressive, unique clinical manifestations, and poor prognosis. Cell division cycle 27 (CDC27) was previously reported to be a significant subunit of the anaphase-promoting complex/cyclosome. However, the specific functions and relevant mechanisms of CDC27 in T-LBL remain unknown. Through immunohistochemistry staining, we identified that CDC27 was overexpressed in T-LBL tissues and related to tumor progression and poor survival. Functional experiments demonstrated that CDC27 promoted proliferation in vivo and in vitro. Further experiment suggested the role of CDC27 in facilitating G1/S transition and promoting the expression of Cyclin D1 and CDK4. Then the effect of CDC27 in inhibiting apoptosis was also identified. Furthermore, we found a positive correlation between the expression of CDC27 and Programmed death ligand-1 (PD-L1) by immunohistochemistry staining. The interaction between CDC27 and PD-L1 was also proved by western blot, luciferase gene reporter assay and immunofluorescence. Taken together, our results showed that CDC27 contributes to T-LBL progression and there is a positive correlation between PD-L1 and CDC27, which offers novel perspectives for future studies on targeting CDC27 in T-LBL.